Effects of Piper sarmentosum extract supplementation on growth performances and rumen fermentation and microflora characteristics in goats. Issue 2 (30th December 2019) - Zhou, Luli; Wang, Dingfa; Hu, Haichao; Zhou, Hanlin
Abstract: This study was carried out to investigate the effect of diet Piper sarmentosum extract (PSE) on the growth performance, antioxidant properties, rumen fermentation and microflora in goats. Forty Hainan black goats with similar body weight were divided into four groups with supplementation of PSE in the concentrate at 0, 300, 600 and 1, 200 mg/kg, respectively, and fed for 56 days. Results showed that average daily gain (ADG) was higher and feed intake/body gain (F/G) was lower in goats fed with PSE at 300 mg/kg ( p  < .05). The activities of glutathione peroxidase (GSH‐Px) and total antioxidant capacity (T‐AOC) in the serum of goats differed among treatments and were greatest linearly when PSE was added at 1, 200 mg/kg ( p  < .05). The level of malondialdehyde (MDA) in the serum of goats differed among treatments and was lowest linearly when PSE was added at 1, 200 mg/kg ( p  < .05). The level of protozoal protein in the rumen of goats differed among treatments and was lowest linearly when PSE was added at 1, 200 mg/kg ( p  < .05). The concentrations of ruminal acetic acid and valeric acid and the ratio of acetate to propionate were reduced with PSE supplementation ( p  < .05). Protozoa, fungi, Ruminococcus flavefaciens and Fibrobacter succinogenes contents differed among treatments and were lowest linearly when PSE was added at 1, 200 mg/kg ( p  < .05). Thus, supplementation of PSE at 300–1, 200 mg/kg to goat concentrate is recommended for improving antioxidative ability and rumen efficiency and reducing protozoal content of goat.